Co-Occurrence of Arthritis and Stroke amongst Middle-Aged and Older Adults in Canada - Roman Matveev; Chris I. Ardern (Stroke Research and Treatment)
Arthritis is a chronic inflammatory condition commonly associated with mobility restriction and reduced activity. To date, the extent to which arthritis is an independent risk factor for stroke is unclear, and important, in light of an aging population. The purpose of this study was to (i) quantify the cross-sectional association between stroke and arthritis and (ii) to determine whether the relationship differed in physically active and inactivemiddle-aged and older adults. Data was derived from the 2010 Canadian Community Health Survey (N=47 188; ≥30 y). Multivariable logistic regression was used to estimate the association between arthritis and stroke in models adjusted for age, physical activity (PA), and demographic factors. Overall, individuals with arthritis were 4 times more likely to report a history of stroke (OR=3.8, 95% CI = 3.06–4.68), whereas those who were engaged in at least moderate PA (≥ 1.5 kcal/kg/day) were less than half as likely (0.45, 0.92−0.62). This effect was moderated by age, as younger (30–65 y: 3.27, 2.22–4.83) but not older adults (>65 y: 1.04, 0.8–1.35) with arthritis had elevated odds of stroke. Both physical inactivity and arthritis are associated with higher odds of stroke, effects of which are the strongest amongst 30–65 year olds.